2021
DOI: 10.3390/cancers13123081
|View full text |Cite
|
Sign up to set email alerts
|

Are Borrmann’s Types of Advanced Gastric Cancer Distinct Clinicopathological and Molecular Entities? A Western Study

Abstract: Most studies on the clinicopathological impact of Borrmann classification for gastric cancer (GC) have been performed in Asian patients with type IV tumors, and immunohistochemical features of Borrmann types have scarcely been analyzed. We assessed the clinicopathological, molecular features and prognostic value of Borrmann types in all patients with advanced GC resected in a Western institution (n = 260). We observed a significant relationship between Borrmann types and age, systemic symptoms, tumor size, Lau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…Besides, we found CT based Borrmann classification was significant in multivariable analysis and contained in model construction. Borrmann classification descripts tumor aggressiveness by tumor size, infiltration scale and the presence of ulceration, which represents distinct biological entities and reflect tumor aggressiveness ( 22 ). A preliminary work ( 21 ) proved Borrmann classification was an independent risk factor for LNM in GC, thus, we continued to analyze Borrmann classification in this study and found it is an independent predictor for LVI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, we found CT based Borrmann classification was significant in multivariable analysis and contained in model construction. Borrmann classification descripts tumor aggressiveness by tumor size, infiltration scale and the presence of ulceration, which represents distinct biological entities and reflect tumor aggressiveness ( 22 ). A preliminary work ( 21 ) proved Borrmann classification was an independent risk factor for LNM in GC, thus, we continued to analyze Borrmann classification in this study and found it is an independent predictor for LVI.…”
Section: Discussionmentioning
confidence: 99%
“…Because tumor thickness was proved to be a risk factor for LNM in a prior study ( 21 ), it was included in this present study continuously, defined as the maximal diameter perpendicular to the longest axis on the maximal cross-section. Borrmann classification on CT was evaluated according to tumor morphology, infiltration scale and presence of ulceration ( 21 , 22 ). Circumscribed mass as classification I, circumscribed mass presented with ulcers as II, infiltrative mass with ulcers as III, and diffuse infiltrative mass as IV ( 16 ).…”
Section: Methodsmentioning
confidence: 99%
“…Overall, 59 patients underwent surgery. Macroscopic type was assessed by Borrmann classification [ 35 ]. Lauren’s classification was used to define the histological type dividing intestinal from diffuse/mixed tumors [ 36 , 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…At the same time when the gross appearance was correlated with Ki-67, maximum cases (90%) expressed low Ki-67 in all growth pattern types. [12,13].…”
Section: Discussionmentioning
confidence: 99%